Determining factors in the enterprising capacity of the students of the Universidad Nacional Mayor de San Marcos - Mavila Hinojoza, Daniel (2009)
In the context of globalization the need to innovate, create wealth and develop the creative potential of human resources is emphasizing the development of entrepreneurship. The purpose of this investigation was to determine the possible factors that explain the abilities of students from San Marcos University and thus help in the formulation of guidelines to enable the University to develop educational and training bases to promote an enterprise culture of their students. Previous research had established three factors to explain entrepreneurship in university students, drawing primarily on this background and in the interaction of the multidisciplinary team that conducted the research, discussed the need to include a fourth factor, all based on the principles of psychometrics. The results indicate four factors that explain the abilities of young entrants to the UNMSM: ability to relate socially, creativity, capacity planning and realization. The fourth factor considered was that of creativity.